Study to Assess the Selected Psychosocial Problems of Working Women and Adopted Coping Strategies by Them in Selected Occupations of Gwalior City with a View to Develop Booklet on it - Meena, Suraj Kumar; Singh, Rashmi (Indian Journal of Nursing Sciences, 2024)
Background: India being a predominantly rural country with a population of more than 1 billion people has access to cheap labor. Looking back at the Indian population and labor literature, India has grown at an annual rate of 2.27% in urban areas and 0.66% in rural areas. Materials and Methods: For the main study investigator had selected the research setting selected Occupations -Primary teachers of schools run by General Medical Council (GMC), Nursing professionals of multispecialty hospital above 100 beds run by GMC. The hospitals and schools were selected on the basis of geographical proximity, feasibility of conducting study, and availability of sample. Results: In the present study, selected psychosocial problems in that about work place 151.33 (16.67%), harassment 34.50 (25.00%), dignity 240.00 (100.00%), support 289.00 (100.00%), decision-making 165.50 (50.00%), sleep disturbances 175.00 (100.00%), concentration 200.00 (20.00%), time difficulty 202.00 (33.33%), relationship 142.00 (20.00%), job security 60.00 (100.00%), and physical problem 180.00 (100.00%). Moreover, coping strategies 13% samples have poor coping strategies, 23.5% samples have average coping strategies, and 63.5% samples have good coping strategies. Conclusion: The major conclusions derived from the present study are Working women have good coping strategies in selected occupations of Gwalior city, There is no significant association with the Selected Demographic Variables such as professional qualifications, designation, type of family, religion and There was a significant association with the selected Demographic Variables such as age, monthly income, and experience at present job.